2015
DOI: 10.3758/s13428-015-0567-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysics in a Web browser? Comparing response times collected with JavaScript and Psychophysics Toolbox in a visual search task

Abstract: Behavioral researchers are increasingly using Webbased software such as JavaScript to conduct response time experiments. Although there has been some research on the accuracy and reliability of response time measurements collected using JavaScript, it remains unclear how well this method performs relative to standard laboratory software in psychologically relevant experimental manipulations. Here we present results from a visual search experiment in which we measured response time distributions with both Psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
190
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(206 citation statements)
references
References 30 publications
13
190
0
3
Order By: Relevance
“…Also, some technologies have been shown to provide inaccurate timing if no countermeasures are taken (Eichstaedt, 2001). The most widely applicable technology (in terms of availability on client machines) offering millisecond resolution is JavaScript (de Leeuw, 2015;Reips & Krantz, 2010). So far, investigations using nonhuman response systems have demonstrated that JavaScript provides adequately accurate timing under most conditions (Reimers & Stewart, 2015), and a recent experiment with human response data has confirmed this conclusion (de Leeuw & Motz, 2015).…”
mentioning
confidence: 99%
“…Also, some technologies have been shown to provide inaccurate timing if no countermeasures are taken (Eichstaedt, 2001). The most widely applicable technology (in terms of availability on client machines) offering millisecond resolution is JavaScript (de Leeuw, 2015;Reips & Krantz, 2010). So far, investigations using nonhuman response systems have demonstrated that JavaScript provides adequately accurate timing under most conditions (Reimers & Stewart, 2015), and a recent experiment with human response data has confirmed this conclusion (de Leeuw & Motz, 2015).…”
mentioning
confidence: 99%
“…Research has indicated that Java Script is an adequate instrument for assessing reaction times (de Leeuw & Motz, 2015;Reimers & Stewart, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Although the general procedure was successfully implemented in an online environment as done in previous attempts (de Leeuw & Motz, 2015;Schubert et al, 2013), the exclusion rate with about 20% was considerably high. These exclusions were mostly based on attention checks pointing at the idea that such checks should be commonly used when recruiting participants on MTurk (Peer, Vosgerau, & Acquisti, 2014).…”
Section: Limitationsmentioning
confidence: 99%
“…We include parameters to control motion direction, coherence level, the total number of dots, dot size, dot color, background color, aperture shape, aperture size, the location of the aperture on the screen, the fixation cross, and how far dots move from one frame to the next. While our raw code can be implemented on any platform that uses JavaScript, incorporating our plugin with the jsPsych library may be particularly advantageous for researchers looking to use this RDK in experiments assessing reaction times; a comparison of reaction times assessed with jsPsych and a standard software package (e.g., PsychToolbox in MATLAB), revealed that while reaction times measured by jsPsych tended to be slightly slower than PsychToolbox, response time variability was quite comparable between both software packages [12]. This indicates that response time measurements in jsPsych are sensitive enough to detect differences caused by experimental manipulations.…”
Section: Implementation and Architecturementioning
confidence: 99%